2013
DOI: 10.1097/ccm.0b013e31828cf104
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Thromboprophylaxis in Medical-Surgical Critically Ill Patients

Abstract: Trial evidence to date suggests that any type of heparin thromboprophylaxis decreases deep vein thrombosis and pulmonary embolism in medical-surgical critically ill patients, and low-molecular-weight heparin compared with bid unfractionated heparin decreases pulmonary embolism and symptomatic pulmonary embolism. Major bleeding and mortality rates do not appear to be significantly influenced by heparin thromboprophylaxis in the ICU setting. Trial methodology, indirectness, and the heterogeneity and imprecision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 33 publications
4
111
2
7
Order By: Relevance
“…Mortality was lower in the patients receiving prophylaxis, although this did not reach statistical significance [514]. All studies included in the meta-analysis were cited in the 2012 guideline, which recommended pharmacologic prophylaxis.…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
See 1 more Smart Citation
“…Mortality was lower in the patients receiving prophylaxis, although this did not reach statistical significance [514]. All studies included in the meta-analysis were cited in the 2012 guideline, which recommended pharmacologic prophylaxis.…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
“…The incidence of DVT acquired in the ICU may be as high as 10% [512]; the incidence of acquired PE may be 2-4% [513,514]. Patients with sepsis and septic shock are likely at increased risk for this complication.…”
Section: We Suggest Mechanical Vte Prophylaxis When Pharmacologic Vtementioning
confidence: 99%
“…The results demonstrated that both LDUH and LMWH prevent DVT, and the incidence of DVT did not differ significantly between LDUH and LMWH. [16][17][18] Data from an RCT and the metaanalysis, however, showed that LMWH is superior to LDUH in the prevention of pulmonary embolism. 17,18 In another meta-analysis comparing LDUH and LMWH in acutely ill medical patients, LMWH was superior to LDUH in preventing DVT but no difference was found in the incidence of pulmonary embolism.…”
Section: Supporting Evidencementioning
confidence: 99%
“…[16][17][18] Data from an RCT and the metaanalysis, however, showed that LMWH is superior to LDUH in the prevention of pulmonary embolism. 17,18 In another meta-analysis comparing LDUH and LMWH in acutely ill medical patients, LMWH was superior to LDUH in preventing DVT but no difference was found in the incidence of pulmonary embolism. 19 Researchers in 2 other studies 20,21 compared rivaroxaban and apixaban with LMWH in acutely ill medical patients and concluded that the newer oral anticoagulants offered no benefit over LMWH.…”
Section: Supporting Evidencementioning
confidence: 99%
“…A recent Meta-analysis showed that prophylactic doses of unfractionated heparin (UFH) reduced the risk of DVT and PE by 51% and 53%, respectively, in medical patients with no significant increase in hemorrhage 5 . Several other clinical trials and Meta-analysis have shown efficacy and safety of prophylaxis with UFH and Low-molecular weight heparins (LMWH) for preventing VTE [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%